수치해석을 통한 저심도 유닛형 지중열교환기의 성능 검토 - 오진환(JinHwan Oh); 서장후(JangHoo Seo); 남유진(Yujin Nam) (설비공학 논문집, 27(3), 2015)
Recently, ground source heat pump (GSHP) systems have attracted much attention, according to the enhanced social demand of renewable energy. GSHP systems can achieve higher coefficient of performance than the conventional air-source heat pump systems by utilizing stable underground temperature. However, the initial cost of GSHP system is higher than that of the conventional systems, especially, in the small-size buildings. Therefore, it is necessary to develop small-size ground heat exchanger with low cost and quick installation. In this study, a unit-type ground heat exchanger was developed and heat exchange rate was calculated by the numerical simulation. As a result, 27.45 W/m of heat exchange rate was acquired in the condition of $0.5m{×}0.2m{×}2m$ unit.